2020
DOI: 10.33545/comed.2020.v3.i1b.124
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for non- communicable diseases among out patients visiting urban health centre in Jammu region: A cross sectional study

Abstract: Introduction: Twentieth century heralded accelerated health transition which brought Non Communicable Diseases (NCDs) to the forefront of global public health challenges. Global trends suggest that these diseases to a large extent are associated with life styles like-unhealthy dietary intake, physical inactivity, tobacco use, high alcohol consumption and are on the rise Objectives: To assess the risk of Non Communicable Diseases among the community using Community Based Assessment Checklist. Methods: 266 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…In our study, 36.7% of study participants belonged to age group 30-39years and this finding was opposite to study conducted by Kaur MP et.al. 8 where 41% of the respondents were more than equal to 50 years similar to findings of Kalidoss VK et.al 10 and Choudhary N et.al 9 where majority participants from age group above 50 years,71% and 64.66 % respectively. This may be because as most individuals > 50yrs from surveyed population of our study were already diagnosed case of NCDs hence were excluded from the study.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In our study, 36.7% of study participants belonged to age group 30-39years and this finding was opposite to study conducted by Kaur MP et.al. 8 where 41% of the respondents were more than equal to 50 years similar to findings of Kalidoss VK et.al 10 and Choudhary N et.al 9 where majority participants from age group above 50 years,71% and 64.66 % respectively. This may be because as most individuals > 50yrs from surveyed population of our study were already diagnosed case of NCDs hence were excluded from the study.…”
Section: Discussionsupporting
confidence: 78%
“…The first validity study of a community-based assessment checklist as a comprehensive approach for assessing NCD risk in rural areas was conducted by Choudhary N et.al. 9 Our study found the overall risk of common NCDs was 60.9% with cbac score ≥ 4 while 39.1% had score <4. The risk of common NCDs was 61.2% in rural area which was higher than in study by Kaur MP et.al.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations